Modern methods of managing the administration of a modern state. The example of Silesia during the Habsburg domination (1629‑1740) (Discourse of Law and Administration, 2025)
In the years 1629‑1740, significant changes took place in Silesia as part of the functioning of the royal and state administration in Silesia. This article focuses on the way of thinking about it, the assumptions represented in official memorials from the period after the outbreak of the Thirty Years’ War (1618‑1740), and the subsequent competences of officials resulting from them. They concerned directly their appointment, diminishing their decision-making power. The shape of the administration in the province was influenced by the fact that the aristocracy and the common nobility, who were directly subordinated to the Czech king and who owed their promotions and aristocratic titles, had their seats in bodies and assumed functions. It was also a group not previously associated with Silesia, and therefore did not understand the essence of the tradition resulting from state privileges, did not adhere to them, often conflicted at the very moment of appearing in the province with the nobility who had settled here for centuries. Their strength did not lie in the respect of the population living in the principalities built over the years, but in the imperial authority.
Keywords: Silesia; Silesian parliament; administration; political system; royal offices; offices of the; estates of the realm